The Internet as a source of health-related information among Internet users in the Lodz region, Poland - Kardas, Grzegorz; Daszyńska, Agnieszka; Koziarska-Rościszewska, Małgorzata (Family Medicine & Primary Care Review, 2017)
Background . The Internet is a widely used medium and a popular source of health-related information for patients. Currently, 59% of European Union citizens use it for such purpose. Due to the disputable quality of medical information found on-line, physicians may face problems with the doctor–patient relationship. Objectives . To find the scale of searching for medical information on-line among Internet users in the Lodz region, Poland, study their opinions concerning this medium and identify the most frequent health-related searches. Material and methods . The study involved 301 patients attending family practice in Lodz – 204 women (67.8%) and 97 men (32.2%), median of age 34 years – with access to the Internet. The research was carried out using the authors’ questionnaire in a primary care clinic and on-line. Results . Out of 301 participants, 93.3% (281) confirmed searching for health-related information on-line. A correlation between age and such habit was found, with the median age of those who do so being 33 years. A positive rating of Internet medical information (71.5%, 201) correlated with age (p < 0.001) and was more common among respondents around the age of 35 years. 53.4% (150) of “e-patients” claimed to search the Internet for a possible diagnosis, and 41.3% (116) for other patients’ experience with the same disease. Conclusions . Younger Internet users are more likely to search for medical knowledge on-line, but this group is more critical of this kind of information. Patients of the Lodz region are most likely to search on-line for information about OTC drugs and chronic diseases. Many of them search for possible diagnoses on their own, along with the experiences of other people with the same conditions they have.